Effects of donkey milk on UVB-induced skin barrier damage and melanin pigmentation: A network pharmacology and experimental validation study - Li, Anqi; He, Hailun; Chen, Yanjing; Liao, Feng; Tang, Jie; Li, Li; Fan, Yumei; Li, Li; Xiong, Lidan (Frontiers in Nutrition, 2023)
Dairy products have been regarded as a controversial nutrient to skin for a long time. However, a clear demonstration of the mechanism of donkey milk (DM) on skincare activity is required. In this study, spectrum and chemical component analyses were applied to DM. Then, effects of DM on UVB‑induced skin barrier damage and melanin pigmentation were first evaluated in vitro and in vivo. To confirm the effect of DM on UVB‑induced skin barrier damage, cell survival, animal models and expression of filaggrin (FLG) were determined after UVB irradiation. To clarify the effect of DM on whitening activities, melanogenesis and tyrosinase (TYR) activity were assessed after UVB irradiation. Further a network pharmacology method was applied to study the interaction between DM ingredients and UVB-induced skin injury via regulating steroid biosynthesis and fatty acid metabolism in keratinocytes and help restore skin barrier function. Meanwhile, an analysis of melanogenesis molecular target network was developed and validated to predict the melanogenesis regulators related to 64 melanin targets which the main contributing role of DM might target melanogenesis, cell adhesion molecules (CAMs), and Tumor necrosis factor (TNF) pathway. In conclusion, these results highlight the potential use of DM as a promising agent for whitening and anti-photoaging applications.